Epistemologiczny charakter logiki buddyjskiej - Lipnicki, Michał (Investigationes Linguisticae, 2010)
The article explores the relation between epistemology and the logical concepts developed by Buddhists. In the Indian philosophy logic is conceived as the theory of valid knowledge and its specific shape is determined by the character of epistemological conceptions. We are concentrated on the ideas developed in VI and VII centuries by the philosophers from the vijñānavāda sect. Though references to some theories of other Buddhist sects are inevitable.